Highly Variable Streptococcus oralis Strains Are Common among Viridans Streptococci Isolated from Primates - Denapaite, Dalia (mSphere, 2016)
Viridans streptococci were obtained from primates (great apes, rhesus monkeys, and ring-tailed lemurs) held in captivity, as well as from free-living animals (chimpanzees and lemurs) for whom contact with humans is highly restricted. Isolates represented a variety of viridans streptococci, including unknown species. Streptococcus oralis was frequently isolated from samples from great apes. Genotypic methods revealed that most of the strains clustered on separate lineages outside the main cluster of human S. oralis strains. This suggests that S. oralis is part of the commensal flora in higher primates and evolved prior to humans. Many genes described as virulence factors in Streptococcus pneumoniae were present also in other viridans streptococcal genomes. Unlike in S. pneumoniae, clustered regularly interspaced short palindromic repeat (CRISPR)–CRISPR-associated protein (Cas) gene clusters were common among viridans streptococci, and many S. oralis strains were type PI-2 (pilus islet 2) variants. S. oralis displayed a remarkable diversity of genes involved in the biosynthesis of peptidoglycan (penicillin-binding proteins and MurMN) and choline-containing teichoic acid. The small noncoding cia-dependent small RNAs (csRNAs) controlled by the response regulator CiaR might contribute to the genomic diversity, since we observed novel genomic islands between duplicated csRNAs, variably present in some isolates. All S. oralis genomes contained a β-N-acetyl-hexosaminidase gene absent in S. pneumoniae, which in contrast frequently harbors the neuraminidases NanB/C, which are absent in S. oralis. The identification of S. oralis-specific genes will help us to understand their adaptation to diverse habitats. IMPORTANCE Streptococcus pneumoniae is a rare example of a human-pathogenic bacterium among viridans streptococci, which consist of commensal symbionts, such as the close relatives Streptococcus mitis and S. oralis. We have shown that S. oralis can frequently be isolated from primates and a variety of other viridans streptococci as well. Genes and genomic islands which are known pneumococcal virulence factors are present in S. oralis and S. mitis, documenting the widespread occurrence of these compounds, which encode surface and secreted proteins. The frequent occurrence of CRISP-Cas gene clusters and a surprising variation of a set of small noncoding RNAs are factors to be considered in future research to further our understanding of mechanisms involved in the genomic diversity driven by horizontal gene transfer among viridans streptococci.